The Influence of Brand Image, Promotion, Price, and Quality of Service on Sahid Polytechnic Lecture Decisions - Juhaeri, Juhaeri; Rinova, Rieke (Universitas Negeri Makassar, 2022)
The purpose of the study was to determine the partial and simultaneous influence of brand image, promotion, price, and service quality on college decisions at Sahid Polytechnic. This research is associative with a quantitative approach. The population in this study were students of the Sahid TA Polytechnic. 2018-2021 with a total sample of 92 respondents. Data collection techniques using questionnaires, data analysis techniques using instrument tests, classical assumption tests, regression tests, coefficients of determination, t tests, and F tests. Based on the results of research partially brand image (X1) and price (X3) variables have no significant effect on the college decision variable (Y) at the Sahid Polytechnic. The promotion variable (X2) and service quality (X4) have an influence on the college decision variable (Y) at Sahid Polytechnic. From these results, it is known that the better and increase the promotion in line with the increasing decision to study at the Sahid Polytechnic. Simultaneous research shows the results of the variable brand image (X1), promotion (X2), price (X3) and service quality (X4) simultaneously and significantly on the college decision variable (Y) at Sahid Polytechnic.